1997
DOI: 10.1364/ol.22.001180
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of room-temperature laser action at 25 µm from Cr^2+:Cd_085Mn_015Te

Abstract: Room-temperature laser action from Cr(2+)-doped Cd(0.85)Mn(0.15)Te has been demonstrated for what is believed to be the first time. We achieved pulsed laser operation centered at ~2.5mu m by pumping into the mid-infrared absorption band of Cr(2+) ions by use of the 1.907- mum output of a H(2) Raman-shifted Nd:YAG laser. The output of the free-running Cr(2+):Cd(0.85)Mn(0.15)Te laser had a width of ~50 nm (FWHM), and the slope efficiency was calculated to be 5.5% under nonoptimum conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 7 publications
0
43
0
3
Order By: Relevance
“…In particular, these chalcogenides doped with Cr 2+ ions have already been shown to produce highly efficient and broadly tunable SE in different lasing modes in the 2-3 µm spectral region [52][53][54]. As before, activated semiconductor crystals, especially of the II-VI family, stimulate the imagination and foster corresponding activity of researchers in the development of SSLs with "electrical" pumping (see, e.g.…”
Section: Anisotropic Chloride Bromide Sulphide Oxychloride Oxyflumentioning
confidence: 89%
“…In particular, these chalcogenides doped with Cr 2+ ions have already been shown to produce highly efficient and broadly tunable SE in different lasing modes in the 2-3 µm spectral region [52][53][54]. As before, activated semiconductor crystals, especially of the II-VI family, stimulate the imagination and foster corresponding activity of researchers in the development of SSLs with "electrical" pumping (see, e.g.…”
Section: Anisotropic Chloride Bromide Sulphide Oxychloride Oxyflumentioning
confidence: 89%
“…In 1996 Deloach et al [1], characterized many transition metal doped II-VI semiconductor gain media identifying multiple materials suitable for midinfrared laser emission. Materials such as Cr:ZnSe, Cr:CdSe, Cr:Cd x Mn 1-x Te and Cr:ZnS were shown to possess many desirable characteristics such as large emission cross-sections, broad gain and absorption bandwidths, no excited state absorption and room temperature operation, with all of these materials having since demonstrated mid-infrared laser operation [2][3][4][5]. Chromium laser technology has matured to demonstrate high power, widely tunable, and narrow line-width operation at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent research has demonstrated the great potential of CMT for application in room-temperature radiation detection. Compared to the widely investigated cadmium zinc telluride (CZT), CMT offers some distinct advantages that make it a good candidate to compete with CZT in such applications.…”
Section: Introductionmentioning
confidence: 99%